ADSORPTION MODEL OF Mn2+, Cd2+ and Hg2+ IN THE WATER - SEDIMENT SYSTEMS ALONG CODE RIVER, YOGYAKARTA - Muzakky Muzakky (Indonesian Journal of Chemistry, 2008)
Prediction of adsorption model of Mn2+, Cd2+ and Hg2+ in water-sediment systems along Code River, Yogyakarta has been experimentally investigated. The aim of this investigation is to predict the transfer models based on isotherm adsorption of Mn2+, Cd2+ and Hg2+ metal ions from water into sediment. In addition, this investigation is expected to be able to inform the initial condition of Code River, dynamics, and the fate of Mn2+, Cd2+ and Hg2+ ions from upstream to downstream. Based on the investigation the transfer of Mn2+, and Cd2+ ions into sediment follows Langmuir adsorption model, with the coefficient determination (R2) of 0,9916 and 0,9799, while the value of the adsorption energy are 20,95 kJ/mol and 16,85 kJ/mol. The transfer of Hg2+ ion tend to follow Freundlich adsorption model. From the adsorption energies, it is proven  that Mn2+ ion was chemically sorpted into the sediment, while Cd2+ ion will tend to be physically sorpted into the sediment. The binding strength of which ise in the order of Mn2+> Cd2+ and the adsorption energy of Hg2+ion couldnot be determined.